2017
DOI: 10.11005/jbm.2017.24.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Costs of Osteoporotic Fracture in Korea: Information from the National Health Insurance Claims Database, 2008-2011

Abstract: BackgroundThe present study estimated healthcare costs of osteoporotic fractures including spine, hip, distal radius and humerus in Koreans over 50 years of age using national claims data.MethodsKorea National Health Insurance data between 2008 and 2011 was searched for all claims records of outpatient visits or hospital admissions of patients ≥50-year-of-age. Osteoporosis-related fractures were identified using certain the International Classification of Diseases, Tenth Revision codes and site-specific physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…The age-adjusted incidence rate per 100,000 persons was 840.49 in 2012 and 869.68 in 2016, while the sex-adjusted incidence rate per 100,000 persons was 360.63 men and 1,185.31 women in 2012 compared to 352.54 men and 1,222.14 women in 2016. Both indices were considerably higher in 2016 compared to 2012, as also reported by Kim et al [9], who analyzed the HIRA data for 2008-2011. They found that the age-adjusted incidence rate increased continuously from 1,127 per 100,000 persons in 2008 to 1,295 per 100,000 persons in 2011 and was higher in women.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The age-adjusted incidence rate per 100,000 persons was 840.49 in 2012 and 869.68 in 2016, while the sex-adjusted incidence rate per 100,000 persons was 360.63 men and 1,185.31 women in 2012 compared to 352.54 men and 1,222.14 women in 2016. Both indices were considerably higher in 2016 compared to 2012, as also reported by Kim et al [9], who analyzed the HIRA data for 2008-2011. They found that the age-adjusted incidence rate increased continuously from 1,127 per 100,000 persons in 2008 to 1,295 per 100,000 persons in 2011 and was higher in women.…”
Section: Discussionsupporting
confidence: 81%
“…In terms of management trends, the rate of bone cement augmentation increased, while the rate of conservative treatment decreased. These findings showed an upward trend, which was seen in the NHIS data for 2008 to 2011 [9]. According to the NHIS data for 2008-2011, the total healthcare costs of osteoporotic fractures increased from $549 million in 2008 to $722 million in 2011.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, the prevalence of osteoporosis and cost of health insurance for patients with osteoporosis as well as its social burden have been steadily increasing. [ 15 ] Therefore, it is best to prevent osteoporosis through aggressive management in young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine in tobacco has been shown to decrease estrogen secretion, which inhibits calcium dissolution in bone, and to accelerate the conversion of estradiol to lower metabolites, thus affecting calcium and vitamin D metabolism. [ 22 ] According to Kim et al[ 15 ], rate of fast food intake was 72%, followed by hamburgers, fried potatoes, chicken, and pizza. Calcium intake was the most insufficient among the nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis and OFs (i.e., DRFs, HFs, spine, and humerus fractures) are becoming more important health problems in the elderly [13]. OFs reduce quality of life and cause medical expenses in the elderly [14,15].…”
Section: Discussionmentioning
confidence: 99%